Language use in shifting contexts: Two multilingual Filipinos' narratives of language and mobility - Rebecca Urip Wattimena; Christine Manara (Universitas Katolik Indonesia Atma Jaya, 2016)
This study explores languages repertoire of two Filipinos who were brought up in a multilingual family and subsequently left their home country to live abroad. Both participants were exposed to more than 4 languages at their home country before they went to live abroad. The study was guided by three research questions: 1) how do these multilinguals use their languages? 2) what kind of linguistic dynamics the participants encountered during their mobility experiences? 3) how do the participants perceive themselves in relation to their linguistic and cultural identity? Narrative-based study was adopted to conduct this research. Data were elicited using open-ended interviews. The major findings show that although participants are still attached with their local languages, shifting of dominant language occurs in line with their mobility experiences. In addition, there is also an indication of language shift that takes place on the fourth generation. The 1st generation languages (participants’ grandparents, i.e. Ibanag and Karay-A) are no longer spoken nd Tagalog is not inherited to the 4th generation of one of the participants.